The Effective Tax Burden of Companies in European Regions An International Comparison - Lammersen, Lothar; Schwager, Robert (ZEW Economic Studies, 2005)
The tax burden on investment or companies is an important factor for the attractiveness of a country or a region. In particular, business location and investment decisions are influenced by the relative tax burdens encountered in different regions. This study presents estimates of the effective average and marginal tax rates on company investment for 143 regions in Europe and the USA. Using the approach pioneered by Michael Devereux and Rachel Griffith, it is shown that companies face a wide variation of effective tax burdens across European regions. The results are explained by analysing the importance of specific tax provisions for the tax burden at the various locations.